Protecting and Meeting Rights of Children during Conflict? Reflections on the Activities of Three Indigenous Social Work Agencies in Northern Uganda - Awich Ochen, Eric (British Journal of Social Work, 2012)
The complex humanitarian emergency in northern Uganda was occasioned by the two decades of conflict. As a result, several development organisations (local and international) responded to the support needs of children and communities affected by the armed conflict in northern Uganda. Some interventions were developed to meet the psycho-social needs of the children at the reception and rehabilitation centres (RRCs) and in the community. Others were designed to respond to the psycho-social challenges of their families and of the returning children. Interventions have also been developed to address the children’s resettlement and reintegration needs. In this paper, I make a critical analysis of the activities of three indigenous organisations, namely CARITAS Gulu archdiocese; Gulu Support the Children Organisation (GUSCO); and Concerned Parents Association (CPA), as they carry out support activities for children associated with fighting forces. I utilize a child rights discourse in analyzing the interventions and their overall implications to social work practice in a complex context. I argue that, while these interventions were relevant to the circumstances of the children and young people, they in many cases fell short of fully empowering them to engage more proactively with their communities.
Keywords: Child rights discourse; Reintegration; Conflict; Agency